PENGARUH GAYA KEPEMIMPINNAN DAN MOTIVASI TERHADAP KINERJA KARYAWAN - Mochammad Soleman; Aris Budiono (LPPM Universitas Asa Indonesia, 2015)
Purpose- The Effect Of Management Style And Motivation Against Staff’s performance In Universitas Islam As-Syafi’iyah Jakarta Design/methodology/approach- Using the method of probability sampling, the sample by Slovin formula is 60 respondents. Data collected by questionaire, and analyzed by multiple regression at the standard of tolerance by 5%. Findings- Both managemen t style and motivation of employees contribut to work performance in Universitas Islam As-Syafi’iyah Jakarta. Limitation of the research- due to a non longitudinal resarch, it is necessary the further research by next year is to be held to enrich this findings. Mangaerial Implication- To boost work performance, it is necessary to monitor the presence and disciple of the employees in Universitas Islam As-Syafi’iyah Jakarta